KARAKTERISTIK PENDERITA PENYAKIT PARU OBSTRUKSI KRONIK YANG DIRAWAT INAP DI RUMAH SAKIT MARTHA FRISKA MEDAN TAHUN 2010-2011 - Yessy Oktorina; Jemadi .; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Chronic Obstructive Pulmonary Disease (COPD) is one of the public health problem in developed countries and developing countries. In 2005 it repoted that there were 210 million COPD in the world. While from Household Health Survey in 2001, COPD was the third from ten disease which potentially caused death in Indonesia. This study was descriptive research with case series design to know the characteristic of COPD patient in RS Martha Friska Medan in 2010-2011. The population and sample were 167 COPD patient data who had been hospitalized in RS Martha Friska in 2010-2011 (total sampling). The highest proportion of the patient with COPD was at age 65-73 years old 35,3% for male 29,3% and female 6%, Bataknes ethnic 52,1%, Moeslim 55,1%, Senior High School 58,1%, civil servant/army/retired 63,4%, from Medan 86,2%, Asthma Bronchial as disease history 67,7%, smoke history 87,5%, cough 91%, average length of stay 8,24 days, expense from Askes 63,4%, becoming out patient 80,8% and CFR=12,6%. There was no significant difference between proportion of the age group with smoke history (p=0,499), sex with smoke history (p=0,504) and sex with disease history (p=0,245). The proportion of COPD patient with asthma bronchialis disease history who had smoked was significantly higher than COPD patient who had not smoked (X2=7,897 ; p=0,005 ; 100% vs 0%). Average length of stay patient who used their own cost were significantly difference for using Jamkesmas, Company and Askes (p=0,003 ; 5,47 days vs 7,25 days ; 5,47 days vs 8,38 days ; 5,47 days vs 9,19 days). It is expected for the party of RS Martha Friska Medan to complete the data note for disease history, smoke history and COPD grade on the medical record and for the government through the department of health, department of social and department of education give the information about the danger of smoking and reduce smoking room. Keyword : COPD patient, characteristic, RS Martha Friska Medan